Altruism Enhances Frontal Alpha Asymmetry and Reduces Sympathetic Activity: A Multimodal EEG‐ECG Study With Implications for Therapeutic Interventions - Junya Orui; Keigo Shiraiwa; Takao Inoue; Masaya Ueda; Keita Ueno; Yasuo Naito; Ryouhei Ishii (Brain and Behavior)
ABSTRACT Introduction This study aimed to investigate neurophysiological differences between altruistic and selfish behaviors by simultaneously measuring electroencephalography (EEG) and electrocardiography (ECG). Specifically, we hypothesized that altruistic behavior would be associated with distinct patterns of cortical activity and autonomic responses. Methods Thirty‐one healthy participants (17 females; mean age: 20.00 ± 1.18 years) completed crafting tasks in a counterbalanced order under altruistic and selfish conditions. We measured and analyzed frontal alpha asymmetry (FAA) scores, cardiac sympathetic index (CSI), and cardiac vagal index (CVI). Additionally, we used eLORETA (exact‐low resolution electromagnetic tomography) to examine current source density and functional connectivity patterns across brain regions. Results The altruistic condition exhibited significantly higher FAA scores (p = 0.031, r = 0.45) and lower CSI (p = 0.048, Cohen's d = 0.37) compared to the selfish condition. Notably, novel correlations were observed between neurophysiological measures and specific brain regions. Specifically, FAA scores were associated with gamma activity in the anterior cingulate cortex during the altruistic condition (p = 0.071) and with precuneus activity during selfish behavior (p = 0.029). Additionally, distinct functional connectivity patterns were associated with autonomic activity in the altruistic condition. Parasympathetic activity negatively correlated with temporal‐gamma connectivity (p = 0.002), and heart rate change negatively correlated with temporal‐prefrontal theta connectivity (p = 0.048). Conclusions Our findings reveal the intricate relationship between cortical activity, functional connectivity, and autonomic responses during altruistic versus selfish behaviors for the first time. This integrative approach sheds new light on the neural mechanisms underlying social cognition. This approach also has the potential to enhance our understanding of and ability to encourage prosocial behavior in various clinical and therapeutic settings.